Antimicrobial Activity of α-Peptide/β-Peptoid Lysine-Based Peptidomimetics Against Colistin-Resistant Pseudomonas aeruginosa Isolated From Cystic Fibrosis Patients - Molchanova, Natalia; Wang, Hengzhuang; Hansen, Paul R.; Høiby, Niels; Nielsen, Hanne M.; Franzyk, Henrik (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa infection is a predominant cause of morbidity and mortality in patients with cystic fibrosis infection with a compromised immune system. Emergence of bacterial resistance renders existing antibiotics inefficient, and therefore discovery of new antimicrobial agents is highly warranted. In recent years, numerous studies have demonstrated that antimicrobial peptides (AMPs) constitute potent agents against a range of pathogenic bacteria. However, AMPs possess a number of drawbacks such as susceptibility to proteolytic degradation with ensuing low bioavailability. To circumvent these undesired properties of AMPs unnatural amino acids or altered backbones have been incorporated to provide stable peptidomimetics with retained antibacterial activity. Here, we report on antimicrobial α-peptide/β-peptoid lysine-based peptidomimetics that exhibit high potency against clinical drug-resistant P. aeruginosa strains obtained from cystic fibrosis patients. These clinical strains possess phoQ and/or pmrB mutations that confer high resistance to colistin, the last-resort antibiotic for treatment of infections caused by P. aeruginosa. The lead peptidomimetic demonstrated a 12-fold improved anti-pseudomonal activity as compared to colistin sulphate as well as favorable killing kinetics